Expert finding by the Dempster‐Shafer theory for evidence combination. Issue 1 (19th October 2017) - Torkzadeh Mahani, Nafiseh; Dehghani, Mostafa; Mirian, Maryam S.; Shakery, Azadeh; Taheri, Khalil
Abstract: The expertise of human experts can be formally extracted from their written documents, research projects, and everyday activities. The process whereby experts are recognized according to their activities is called expert finding. In this paper, we propose an approach to identify the experts in a given field according to the content of 3 easily accessible sources of information: (a) "Publications, " (b) "Social interactions, " and (c) "Scientometric information." We employed the Dempster‐Shafer theory to combine the results obtained from individual sources to find a final unified ranking. In Digital Bibliography & Library Project standard data, it is shown that the Dempster‐Shafer combination creates a desired synergy between 2 bodies of knowledge, which improves the precision of the top‐ranked results.